“เถรอดเพล” จากของเล่นเป็นศาลา - อินพันทัง, วีระ; เกษมศุข, อภิรดี; จารุนุช, สุคตยุติ (NAJUA: Architecture, Design and Built Environment, 2017)
การได้เห็นแท่นตั้งศพในงานสวดพระอภิธรรมที่วัดไทร จังหวัดนครปฐม ซึ่งประกอบสร้างจากข้อต่อไม้แบบเถรอดเพล ก่อให้เกิดแรงบันดาลใจอันเป็นที่มาของงานวิจัยนี้ โดยมีวัตถุประสงค์หลักในการแสวงหาความรู้เกี่ยวกับข้อต่อไม้ดังกล่าวเพื่อประยุกต์สู่งานออกแบบสถาปัตยกรรม ด้วยวิธีการวิจัยเชิงสร้างสรรค์ เริ่มจากขั้นตอนการรวบรวมข้อมูลทั้งจากเอกสารทางวิชาการต่างๆ รวมทั้งการสำรวจภาคสนาม เพื่อประมวลความรู้ว่าด้วยเรื่องเถรอดเพล ลำดับต่อไปเป็นขั้นตอนการวิเคราะห์ข้อมูลเพื่อทำความเข้าใจรูปแบบและศักยภาพของข้อต่อไม้ชนิดนี้ ท้ายที่สุดเป็นขั้นตอนการสังเคราะห์ข้อมูล ซึ่งเป็นการออกแบบสถาปัตยกรรมศาลาไม้โดยใช้ข้อต่อแบบเถรอดเพลเป็นกลไกหลักในการประกอบสร้าง ผลการวิจัยแสดงให้เห็นว่า ข้อต่อไม้เถรอดเพลมีศักยภาพในการประยุกต์ใช้ในงานสถาปัตยกรรมได้เป็นอย่างดี สัมฤทธิ์ผลเป็นศาลาโถง 4 เสาหลังคาทรงจั่วที่สร้างขึ้นจากไม้หน้าตัดรูปสี่เหลี่ยมจัตุรัส ซึ่งมีข้อต่อปรากฏโดดเด่นจนกลายเป็นลักษณะเฉพาะที่ไม่เหมือนใคร และด้วยการใช้ข้อต่อไม้เป็นกลไกหลักในการประกอบสร้างยังผลให้บรรลุเป็นสถาปัตยกรรมที่สามารถถอดประกอบได้โดยสมบูรณ์ ‘Thein Ot Phein’ - from wooden-block puzzle to single span pavilion Vira Inpuntung Department of Architecture, Faculty of Architecture, Silpakorn University Apiradee kasemsook Department of Architecture, Faculty of Architecture, Silpakorn University Sukotyut Charunut Department of Architecture, Faculty of Architecture, Silpakorn University The coffin stand at Wat Sai, Nakhon Pathom province, with joints constructed like wooden-block puzzles called ‘Thein Ot Phein’ was the inspiration for this research. The main objective of the study is to attempt to apply this type of joint to architectural design. Based on the method for creative research, literature reviews and field surveys were carried out to collect information on wooden puzzles. Analysis were then made in order to understand the character and potential of wooden puzzles, especially the Thein Ot Phein. From the knowledge obtained, a design for construction of a pavilion with joints based on Thein Ot Phein wooden puzzle was made. The result showed that the Thein Ot Phein wooden puzzle joint has promising potential for application to architectural construction. A single span pavilion with 4 posts and gable roof constructed from square cross-section wooden members and joints that are unique, allows the architecture to be assembled and disassembled without difficulty.